A data visualization tool for biomass valorization in Brazil - Bif, Roger Sampaio; Bruschi, Larissa Thais; dos Santos, Moisés Teles (Computer Aided Chemical Engineering, 2024)
Brazil’s diverse climate zones, vast territory, varied soils, and abundant water resources contribute to its rich biodiversity, making it ideal for biomass exploitation. This work deals with the creation of a user-friendly, interactive data visualization tool for biomass valorization. This involves collecting georeferenced data on biomass production and availability and developing an ontology to represent the Brazilian biomass supply chain. The Python programming language with libraries like Pandas, Matplotlib, and Streamlit, are used for data analysis, mapping, and creating web-based visualization applications. The proposed tool provides dynamic maps, showing biomass distribution and availability, highlighting regional resource disparities, assisting in region-specific planning and decision-making. This tool will be further integrated into optimization frameworks, helping to identify opportunities and to develop effective strategies for biomass valorization in Brazil, supporting the decision-making process.